EFFECT OF DIETARY LIPID CONTENTS ON GROWTH OF ESTUARY GROUPER Epinephelus coioides JUVENILES - Ketut Suwirya; Nyoman Adiasmara Giri; Agus Prijono; Muhamad Marzuqi (Research Center for Fisheries, 2005)
Lipid is dietary component for energy and essential fatty acid sourced. Requirement of lipid for fish varies depending on species and size